(untitled) (Revista de História Regional, 2021)
The article addresses the role of the public power in the process of standardization of urban space that occurred in the port city of Corumbá (Brazil) in the final decades of the Empire. It addresses issues related to public hygiene and urban health from documentary sources produced by the municipality of Corumbá in the context of the insertion of the city in international trade routes. The Introduction of the article presents information on the economic, social and institutional changes that occurred in the city after the reopening of navigation on the Paraguay river. The first section deals with the relationship between Municipalities and public hygiene. The second deals with the distance between the laws that dealt with public hygiene and the current social practices. The final section of the text presents the reactions of the corumbaense society and the public power to the cholera epidemic that hit the city in the 1886/1887 biennium.